Histological analysis of thrombus composition in acute ischemic stroke with large vessel occlusion: impact of r-tPA treatment - Zhao, Changzhi; Chen, Guofang; Guo, Zhiliang; Chen, Sha; Ping, Lei; Li, Qiao; Zhang, Xiaoying; Ding, Manhua; Zhang, Yang (Frontiers in Neuroscience, 2025)
Background and purposeMechanical thrombectomy advances enable detection of thrombus composition changes post-intravenous thrombolysis, but evidence remains limited. This study retrospectively analyzed thrombi obtained from mechanical thrombectomy in patients with acute ischemic stroke to explore the impact of intravenous thrombolysis (IVT) on the composition of thrombi in patients with different TOAST classifications and the association between changes in thrombus components and clinical outcome data.Materials and methodsThrombus samples from 141 patients undergoing mechanical thrombectomy (n = 60) or bridging therapy (n = 81) at two hospitals between December 2020 and January 2024 were included. Baseline data and outcome data were collected. Components were analyzed via HE staining and immunohistochemistry for CD61 and FGB, quantifying area percentages of red blood cell (RBC), white blood cell (WBC), platelet-fibrin complexes (PLT + FIB), platelet (PLT), and fibrin (FIB). Thrombus components were compared between the mechanical thrombectomy and bridging therapy groups according to TOAST subtypes, and a combined analysis was conducted with clinical prognosis and surgical conditions.ResultsNo significant baseline differences (p > 0.05). Significant component differences between mechanical thrombectomy and bridging therapy across subtypes: in large artery atherosclerotic (LAA), FIB higher in mechanical thrombectomy (p = 0.001); in cardioembolic (CE), PLT and FIB higher in mechanical thrombectomy (p = 0.003, p < 0.001). Subtype comparisons showed differences: LAA vs. CE in RBC, PLT + FIB, PLT, FIB (p < 0.05); LAA vs. stroke of undetermined source (SUE) in PLT and FIB (p < 0.05); CE vs. SUE in FIB (p < 0.05).ConclusionThis study quantified the thrombus components of different etiologies and found that IVT could reduce the FIB content in thrombi of large artery occlusion cerebral infarction, especially in the LAA type. The platelet content in the LAA type was higher than that in the CE and the SUE types. The FIB level in the SUE type was higher than that in the CE type. FIB was not only present in the PLT area but also in the RBC area. IVT may improve thrombectomy success by disrupting thrombus structure, but it can increase fragment embolization and prolong procedure time.